Photosystem II Functionality in Barley Responds Dynamically to Changes in Leaf Manganese Status - Schmidt, Sidsel B.; Powikrowska, Marta; Krogholm, Ken S.; Naumann-Busch, Bianca; Schjoerring, Jan K.; Husted, Søren; Jensen, Poul E.; Pedas, Pai R. (Frontiers in Plant Science, 2016)
A catalytic manganese (Mn) cluster is required for the oxidation of water in the oxygen-evolving complex (OEC) of photosystem II (PSII) in plants. Despite this essential role of Mn in generating the electrons driving photosynthesis, limited information is available on how Mn deficiency affects PSII functionality. We have here used parameters derived from measurements of fluorescence induction kinetics (OJIP transients), non-photochemical quenching and PSII subunit composition to investigate how latent Mn deficiency changes the photochemistry in two barley genotypes differing in Mn efficiency. Mn deficiency caused dramatic reductions in the quantum yield of PSII and led to the appearance of two new inflection points, the K step and the D dip, in the OJIP fluorescence transients, indicating severe damage to the OEC. In addition, Mn deficiency decreased the ability to induce non-photochemical quenching (NPQ) in the light, rendering the plants incapable of dissipating excess energy in a controlled way. Thus, the Mn deficient plants became severely affected in their ability to recover from high light-induced photoinhibition, especially under strong Mn deficiency. Interestingly, the Mn-efficient genotype was able to maintain a higher non-photochemical quenching than the Mn-inefficient genotype when exposed to mild Mn deficiency. However, during severe Mn deficiency, there were no differences between the two genotypes, suggesting a general loss of the ability to disassemble and repair PSII. The pronounced defects of PSII activity were supported by a dramatic decrease in the abundance of the OEC protein subunits, PsbP and PsbQ in response to Mn deficiency for both genotypes. We conclude that regulation of photosynthetic performance by means of maintaining and inducing NPQ mechanisms contribute to genotypic differences in the Mn efficiency of barley genotypes growing under conditions with mild Mn deficiency.